Analysis of Nursing Care for Adolescent Females Experiencing Dysminore with Nursing Problems of Acute Pain with Giving Green Coconut Water in the Work Area of UPTD Puskesmas Kuta Utara - Mahayoni, Anak Agung Ayu Agung Istri; Sari, Ni Luh Putu Dian Yunita; Prihandani, I GAA Sherlyna (PROMOTOR, 2025)
Menstruation can cause significant disturbances for women. Menstruation usually begins with pain called dysmenorrhea. Dysmenorrhea is a condition of severe pain and can interfere with daily activities in women, especially adolescent girls. One safe and easy non-pharmacological therapy is the administration of green coconut water. This scientific paper was conducted to determine nursing care for adolescent girls with dysmenorrhea pain problems. Implications can be given during the first day of menstruation, drink 2 times a day, 1 glass (200cc), morning and evening, for 3 consecutive days. During the meeting, the nurse provided education and a demonstration of how to administer green coconut water, an evaluation of the action, adolescent girls who initially experienced dysmenorrhea pain with a pain scale of 5 and 6 after the action decreased to a scale of 1 and 0. This shows that the administration of green coconut water is very effective in reducing dysmenorrhea pain. It is hoped that this research can be used for health services, nursing education and the community to overcome dysmenorrhea pain in adolescent girls.